Tamarind Enzymatic Inhibitors: Activities and Health Application Perspectives. (1st November 2022) - Carvalho, F. M. C. D.; Maciel, B. L. L.; Morais, A. H. D. A.
ABSTRACT: Tamarind is a fruit with a wide variety of uses, and the presence of enzyme inhibitors in Tamarind seeds gives the fruit bioactive activities. Protease inhibitors have been recognized as molecules that can potentially contribute to health. Trypsin inhibitors present different physiological effects, such as anti-inflammatory and satietogenic effects, which make them potent candidates for the treatment and prevention of chronic diseases, despite the challenging methodologies in characterizing these new molecules. This paper aims to address the activities and health application perspectives of Tamarind enzyme inhibitors using a systematic integrative literature review.